Tibor Gerencsér, Marcin Grad, Miklos Mitrovits, Flaga węgierska nad Wisłą. Z dziejów placówki dyplomatycznej Węgier nad Wisłą [The Hungarian Flag on the Vistula: From the History of the Hungarian Diplomatic Mission in Poland] (Warsaw: Wydawnictwo MOST, 2017), 223 pp. - Pudłocki, Tomasz (Rocznik Filozoficzny Ignatianum, 2025)
(...)